Development and Application of an Intelligent Evaluation and Control Platform for Tunnel Smooth Blasting. (9th February 2021) - Zou, Baoping; Luo, Zhanyou; Wang, Jianxiu; Hu, Lisheng
Abstract : Many tunnels around the world are still being constructed by drilling and blasting because these methods have an unmatched degree of flexibility relative to machine excavations using tunnel boring machines. At present, a large gap exists between evaluation theory and the control application of tunnel smooth blasting (TSB) quality. In this study, a handheld mobile platform that is based on the Android system and is written in the Java language is proposed to evaluate and control the performance of TSB. The function of this handheld mobile platform mainly includes data input, data modification, data deletion, weight setting for smooth blasting evaluation, smooth blasting quality assessment, and smooth blasting quality control. Using the proposed mobile platform, end users can evaluate and control TSB quality after each blast. The proposed handheld mobile platform is also applied to the real case history of line 6 in Guangzhou, China.